The impact of green HRM and intellectual capital on the environmental performance of the organizations: A mediating impact of green innovation - Anum, Zarmeena; Nasir, Aemin; Ejaz, Faisal; Fodor , Zita Júlia; Hossain, Md Billal (International Journal of Innovative Research and Scientific Studies, 2025)
This research elucidates the importance of Green HRM and Green Intellectual Capital in encouraging eco-friendly practices in the hospitality sector. Additionally, it highlights the value of Green Innovation as a tool to enhance the beneficial impacts of Green HRM and Green Intellectual Capital on environmental performance. A survey was conducted among 257 employees, and the collected data were analyzed using SPSS and Smart PLS. The findings reveal that GHRM and GIC significantly enhance environmental performance, demonstrating the positive effects of green practices on the environment. Furthermore, Green Innovation was found to mediate the relationship between GHRM, GIC, and environmental performance, underscoring the role of innovation in promoting environmental sustainability. This study investigates the impact of Green Human Resource Management (GHRM) and Green Intellectual Capital (GIC) on the environmental performance of firms in the Pakistani hotel industry, focusing on the mediating role of Green Innovation. These results highlight the importance of integrating green practices into HRM and intellectual capital management, as well as the value of innovation in amplifying these efforts. The study’s implications are crucial for hospitality businesses, as they aim to implement sustainable strategies in an increasingly environmentally conscious market.